Evaluation of work-related musculoskeletal disorders and ergonomic risk levels among instrumentalist musicians (Annals of Medical Research, 2021)
Aim: The study aimed to evaluate work-related musculoskeletal disorders and ergonomic risk levels in instrumentalist musicians.Material and Methods: This is a cross - sectional study. The present study consists of 46 musicians, including 11 violinists, 11 side flutists, 13 pianists and 11 baglama players between the ages of 18 and 50 years who are play at least one of the instruments. The socio-demographic characteristics of the musicians and the data of instrument were questioned by using a descriptive questionnaire. The Quick Exposure Check method was used to analyze the ergonomic risk and Expanded Nordic Musculoskeletal System Questionnaire was used to question musculoskeletal diseases.Results: 48.2% of the participants were male and 52.8% were female. 79.3% of all participants had a daily instrument playing time more than 2 hours. Only 9.6% of the musicians had a low level of ergonomic risk. The most common musculoskeletal problems were seen on the wrist, neck and shoulders. The ergonomic risk levels of the musicians who reported pain were also high. Ergonomic risk levels were significantly higher in musicians who reported low back pain and hip-thigh pain (p 0.05). There was a significant difference between the musical instrument types and ergonomic risk levels of musicians, and it was found that the level of ergonomic risk was higher among piano and violin users (p 0.05). Conclusion: In our study, the ergonomic risk levels and the incidence of musculoskeletal disorders related to work of musicians were found to be remarkably high. For this reason, preventive rehabilitation studies should be conducted in musicians. We think that our study will shed light on intervention research in which ergonomic risk management is planned.
Keywords: Work-related musculoskeletal disorders; ergonomic risk; musicians.